Enhancing Both TM- and TE-Polarized Light Extraction Efficiency of AlGaN-Based Deep Ultraviolet Light-Emitting Diode via Air Cavity Extractor With Vertical Sidewall - Yonghui Zhang; Yuxin Zheng; Ruilin Meng; Ce Sun; Kangkai Tian; Chong Geng; Zi-Hui Zhang; Guoxu Liu; Wengang Bi (IEEE Photonics Journal)
In this work, we investigate the effect of sidewall angle, height and space of an air cavity extractor (AC-Extractor) on the polarization-dependent light extraction efficiency (LEE) for AlGaN-based deep-ultraviolet light-emitting diodes (DUV LEDs) using three-dimensional finite difference time-domain method. Compared to the reported inclined sidewall metal reflector (SM-Reflector), DUV LED with AC-Extractor shows better light extraction at any height and inclined angle due to different light extraction mechanisms. The light in SM-Reflector DUV LED is extracted mainly through mirror reflection. However, total internal reflection from the sidewall dominants the contribution to LEE for the AC-Extractor with smaller inclined angle such that the space has little impact, while Fresnel scattering is more important for the AC-Extractor with larger inclined angle and that the additional out-light channel as well as the space play a critical role in enhancing the LEE. And the analysis is further developed into a three-escape-cones analytic model theory. In particular, the AC-Extractor with vertical sidewall is more beneficial to enhance the LEE of DUV LED than that with inclined sidewall, which can be rationally explained based on the three-escape-cones analytic model.